Huge left-sided sliding inguinal bladder hernia - B. G. Guliev; I. A. Soloviev; E. O. Stetsik; A. A. Andriyanov (Вестник урологии)
Sliding inguinal bladder hernia (IBH) is a scarce pathology whose prevalence is higher in men and increases with age. Subject literature searches in PubMed, eLibrary, and MedLine databases covering 1990 to 2023 selected 27 articles for analysis. We studied the prevalence of sliding IBH, its diagnostic methods, and therapeutic tactics. The clinical case also presents our own observation of giant sliding IBH. In a 70-year-old man, the bladder was almost completely displaced into the hernia sac, and chronic kidney disease occurred due to urinary retention. After drainage of bladder, normalisation of creatinine and stabilisation of the patient's general condition, we performed hernioplasty.